Revealing the Power of Deep Learning in Quality Assessment of Mango and Mangosteen Purée Using NIR Spectral Data - Pimpen Pornchaloempong; Sneha Sharma; Thitima Phanomsophon; Panmanas Sirisomboon; Ravipat Lapcharoensuk (Horticulturae, 2025)
The quality control of fruit purée products such as mango and mangosteen is crucial for maintaining consumer satisfaction and meeting industry standards. Traditional destructive techniques for assessing key quality parameters like the soluble solid content (SSC) and titratable acidity (TA) are labor-intensive and time-consuming; prompting the need for rapid, nondestructive alternatives. This study investigated the use of deep learning (DL) models including Simple-CNN, AlexNet, EfficientNetB0, MobileNetV2, and ResNeXt for predicting SSC and TA in mango and mangosteen purée and compared their performance with the conventional chemometric method partial least squares regression (PLSR). Spectral data were preprocessed and evaluated using 10-fold cross-validation. For mango purée, the Simple-CNN model achieved the highest predictive accuracy for both SSC (coefficient of determination of cross-validation (RCV2) = 0.914, root mean square error of cross-validation (RMSECV) = 0.688, the ratio of prediction to deviation of cross-validation (RPDCV) = 3.367) and TA (RCV2 = 0.762, RMSECV = 0.037, RPDCV = 2.864), demonstrating a statistically significant improvement over PLSR. For the mangosteen purée, AlexNet exhibited the best SSC prediction performance (RCV2 = 0.702, RMSECV = 0.471, RPDCV = 1.666), though the RPDCV values (<2.0) indicated limited applicability for precise quantification. TA prediction in mangosteen purée showed low variance in the reference values (standard deviation (SD) = 0.048), which may have restricted model performance. These results highlight the potential of DL for improving NIR-based quality evaluation of fruit purée, while also pointing to the need for further refinement to ensure interpretability, robustness, and practical deployment in industrial quality control.
Keywords: Spectroscopy and Chemometric Analyses; Smart Agriculture and AI; Leaf Properties and Growth Measurement